2014
DOI: 10.1186/1471-2334-14-371
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal excess mortality patterns of the 1918–1919 influenza pandemic in Spain

Abstract: BackgroundThe impact of socio-demographic factors and baseline health on the mortality burden of seasonal and pandemic influenza remains debated. Here we analyzed the spatial-temporal mortality patterns of the 1918 influenza pandemic in Spain, one of the countries of Europe that experienced the highest mortality burden.MethodsWe analyzed monthly death rates from respiratory diseases and all-causes across 49 provinces of Spain, including the Canary and Balearic Islands, during the period January-1915 to June-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 37 publications
2
58
2
8
Order By: Relevance
“…Deaths were more likely to occur within the same week and a few hundred meters than expected given the underlying spatial and temporal clustering, speaking to the importance of neighborhood-level transmission even in a mobile, urban population. Previous studies found significant autocorrelation in influenza mortality across county boroughs in England and Wales (42) and provinces in Spain (20), but this study is unique in showing a spatial dependence in the spread of individual influenza cases during the 1918 pandemic.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Deaths were more likely to occur within the same week and a few hundred meters than expected given the underlying spatial and temporal clustering, speaking to the importance of neighborhood-level transmission even in a mobile, urban population. Previous studies found significant autocorrelation in influenza mortality across county boroughs in England and Wales (42) and provinces in Spain (20), but this study is unique in showing a spatial dependence in the spread of individual influenza cases during the 1918 pandemic.…”
Section: Discussionmentioning
confidence: 88%
“…The association between R and population density may be a result of an increased number of effective contacts between individuals in denser population tracts, but the relationship is confounded by the strong associations between population density and other sociodemographic factors and the largely nonsignificant association between population density and weekly R estimates (Tables S7 and S8). Moreover, the increased transmissibility of influenza in more densely populated census tracts did not translate into significantly higher mortality risk, although population density has been linked to pandemic influenza mortality at greater spatial scales (7,11,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Underlying population risk factors and socioeconomic conditions were likely more important drivers of pandemic mortality rates than environmental factors. For instance, prior studies have suggested that indigenous groups could have been affected disproportionately from past influenza pandemics …”
Section: Discussionmentioning
confidence: 99%
“…For example, population density and background death rates explained 70% of the variation in cumulative pandemic excess mortality rates in province-level data from Chile (10). In another study, latitude, population density, and the proportion of children explained about 40% of between-province variation in cumulative excess death rates in Spain (11). Very little, however, has been done to understand the drivers of pandemic-related mortality rates at the fine scale of households or census tracts, an issue tackled by Grantz et al (6).…”
mentioning
confidence: 99%